Surgical Treatment of Severe Idiopathic Flexible Flatfoot by Evans–Mosca Technique in Adolescent Patients: A Long-Term Follow-Up Study. (20th January 2021) - De Luna, Vincenzo; De Maio, Fernando; Caterini, Alessandro; Marsiolo, Martina; Petrungaro, Lidio; Ippolito, Ernesto; Farsetti, Pasquale
Abstract : Flexible idiopathic flatfoot is very common in growing age and rarely causes pain or disability. Surgery is indicated only in severe symptomatic cases that are resistant to conservative treatment, and numerous surgical procedures have been proposed. Lateral column calcaneal lengthening as described by Evans and modified by Mosca is a widely used surgical technique for the correction of severe symptomatic flexible flatfoot. In the present study, we report the long-term clinical and radiographic results in 14 adolescent patients (mean age: 12.8 years) affected by severe symptomatic flexible flatfoot, surgically treated by Evans–Mosca procedure, for a total of 26 treated feet (12 cases bilateral and 2 unilateral). In all cases, surgery was indicated for the presence of significant symptoms resistant to nonsurgical management. Clinical evaluation was made according to the American Orthopedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Scale, the Foot and Ankle Disability Index (FADI) Score, and Yoo et al.'s criteria. Radiographic evaluation was made using anteroposterior and lateral weight-bearing radiographs of the feet to evaluate Meary's angle and Costa–Bertani's angle and to evaluate possible osteoarthritic changes in the midtarsal joints. At follow-up (mean: 7 years and 7 months), we observed a satisfactory result in all patients. The mean average score of the AOFAS Ankle-Hindfoot Scale improved from 60.03 points to 95.26; the mean FADI score improved from 71.41 to 97.44; and according to Yoo et al.'s criteria, the average clinical outcome score was 10.96. At radiographic examination, nonunion of the calcaneal osteotomy was never observed. Meary's angle improved from an average preoperative value of 25° to 1.38° at follow-up; Costa–Bertani's angle improved from an average preoperative value of 154.2° to 130.9° at follow-up. In no case, significant radiographic signs of midtarsal joint arthritis were observed. According to our results, we believe that Evans–Mosca technique is a valid option of surgical treatment for severe idiopathic flexible flatfoot and allows a satisfactory correction of the deformity with a low rate of complications.